Salvage Reconstruction of Composite Defects of the Anterior Mandible, Floor of Mouth, and Lip - Khalid, Farrukh A.; Ahmed, Omar A.; Khurshid, Almeotan P.; Mujahid, Abdul M.; Ahmad, Junaid; Saleem, Muhammad; Yousaf, Muhammad A.; Tarar, Moazzam N.; Shahzad, Farooq (Archives of Plastic Surgery, 2024)
Anterior mandible defects result in loss of support for the tongue, floor of the mouth and lower lip, resulting in impairment of airway, feeding, and speech. We treated four patients with these “Andy Gump” deformities. Reconstruction was performed with two free flaps: a fibula osteocutaneous flap for the anterior mandible and floor of the mouth, and a soft tissue free flap for the lip, chin, and anterior neck. The lower lip was suspended cranially with fascia or tendon grafts ± mini-temporalis turndown flaps. All flaps survived completely. All patients were tube feed-dependent before surgery; they all resumed an oral diet. All tracheostomies were decannulated. Lip competence was restored as evidenced by cessation of drooling. Speech improved from unintelligible to intelligible with frequent repetitions. Objective assessment was performed with the functional intraoral Glasgow scale; the mean FIGS score improved from 3.25 (range 3–4) to 11 (range 9–13). We conclude that composite anterior mandible and tongue defects have large tissue requirements that require multiple free flaps. Reconstruction leads to significant improvement in function.
Keywords: Andy Gump; anterior mandible; free flap; functional intraoral Glasgow scale; lip suspension